EVALUASI KINERJA KOMISI PEMILIHAN UMUM KABUPATEN BADUNG DALAM PROSES PEMUTAKHIRAN DAFTAR PEMILIH TETAP (DPT) DESA DALUNG PADA PEMILIHAN BUPATI DAN WAKIL BUPATI KABUPATEN BADUNG TAHUN 2015 - Karlina, Ni Made Devi; Pascarani, Ni Nyoman Dewi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2017)
ABSTRACT The permanent registers of voters list is the main problem when The National Election Commission of Indonesia (KPU) organized election activities. On December 9th, 2015, the KPU of Badung Regency has found many problem when the organized election Regent and Vice Regent of Badung Regency in updating data such as duplicate data, died voters are reappears as voters, and citizens who moved domicile are still registered in voter list. The problem in the background for this research is the turnaround time for the determination of the permanent voters list and also due to the many migrants live in the village. The purpose of this research was to evaluate the performance the KPU of Badung Regency in the process of updating the voters list remains for data Dalung village. This research used qualitative descriptive method with depth interview to informants. This research evaluated the performance of the KPU Badung Regency used performance evaluation theory (Agus Dwiyanto) consisting of indicators productivity, quality of service, responsivity, responsibility, and accountability. The results of this research indicate that the KPU performance of Badung Regency is not maximal due to factors such as voters' data while the KPU received from the Civil Registry does not sync, many people have not reported on administrative information of residence, and from KPU officials were less thorough in the input data. Keywords: Performance Evaluation, the National Election Commission, the permanent register of voters list.